Photocatalytic hydroxylation of arylboronic acids using continuous flow reactors - Penders, Inès G. T. M.; Amara, Zacharias; Horvath, Raphael; Rossen, Kai; Poliakoff, Martyn; George, Michael W. (Royal Society of Chemistry, 2014)
The photocatalytic oxidation of mono- and di-substituted arylboronic acids to phenols has been investigated using a continuous flow photoreactor fitted with white LEDs. An EtOH–H2O solvent system accelerated conversion at 2 MPa; whereas reactions at atmospheric pressure allowed for moderately efficient desymmetrisation.